MO928: Patients' and Healthcare Professionals' Perspectives on Nephrogeriatric Assessment as Shared Decision Making Tool for Older Patients With Kidney Failure: A Qualitative Study. (3rd May 2022) - Berkhout-Byrne, Noeleen; Voorend, Carlijn; Meuleman, Yvette; Mooijaart, Simon; Brunsveld-Reinders, Anja; Jan W Bos, Willem; van Buren, Marjolijn
Abstract: BACKGROUND AND AIMS: Dialysis might not benefit all older patients with kidney failure, particularly those with multi-morbid conditions and frailty. Awareness of the presence of geriatric impairments has the potential to improve outcomes by tailoring treatment plans and decisions for individual patients. Geriatric assessment has been recommended in guidelines to support shared decision making (SDM) in older patients with kidney failure. We aimed to describe the perspectives of patients and healthcare professionals on the Nephro-Geriatric Assessment (NGA) as a SDM tool for treatment choice in older patients approaching kidney failure (eGFR)<20 mL/min/1.73 m 2 ). METHOD: Patients ( N = 18) with kidney failure, caregivers ( N = 4) and professionals ( N = 25) were purposively sampled from three university medical centre initiatives and seven regional hospitals from different provinces in the Netherlands. Six semi-structured focus groups were held to discuss participants' experiences with and perspectives on NGA as an aid to SDM in their choices to start or forego dialysis. Transcripts were analysed inductively using thematic analysis. RESULTS: Professionals reported that NGA, performed prior to SDM about kidney replacement therapy (KRT), creates awareness of patients' possibilities but also of their limitations. Somatic frailty is unearthed alongside in-depth knowledge about patients' social system and psychological wellbeing––information they consider vital for good quality SDM relative to KRT. Professionals reported NGA as being a valuable tool to initiate discussions on treatment decisions and patient goals, and improve awareness to (re)consider different treatment options. Although patients and caregivers had positive attitudes towards NGA, they were mostly unaware of the purpose and role that NGA could play in SDM about KRT. Several interconnecting themes, which could facilitate or hinder SDM in kidney failure were identified and grouped under three main themes: (1) patient psycho-social situation: social support system and who influences decisions (e.g. choosing to dialyze due to family pressure), trusting patient–professional relationships, patient emotions (e.g. anxiety about being a burden to family and society), quality of life and life goals; (2) on modality choice: medical history and frailty, patient character and attitudes (e.g. an optimistic or pessimistic view of life), health-related information and education, continual assessment of situation; (3) organization of health care: multidisciplinary approach, consultation with geriatrician, early referral to kidney failure care and consultation time. CONCLUSION: Professionals confirmed the benefits of NGA as a tool to identify geriatric impairments in older patients approaching kidney failure and how integration of its outcomes can facilitate a more holistic approach to inform choices about KRT based on patient values, expectations and goals. Recognition of supporting factors and resolution of impeding factors to SDM about KRT can be beneficial for good SDM. Our study underscores the importance of clear patient–professional communication. Conducting NGA provides anchors to include information on geriatric impairments, which is potentially valuable for the prevention of decisional regret.